Politics of law affirmative action on empowerment of laut tribes in Lingga regency - Adhayanto, Oksep; Shalihah, Fithriatus (Linguistics and Culture Review, 2021)
Indonesia is a country that has cultural diversity, ethnicity, religion, and regional languages. Indonesia, with its diversity, has much ethnic powerlessness, so that it affects and creates disparities in society. Therefore, the government needs to be encouraged to approach formulating policies to empower tribal communities in Indonesia. This study aims to find out how the legal politics of affirmative action towards the empowerment of the Laut tribe in Lingga Regency. This research is a qualitative descriptive study with a normative juridical and empirical juridical approach. Primary data or materials in this study were obtained directly from informants through field research. The types of data used are library research, interviews, and focus group discussions. The data were analyzed using the Miles and Huberman models, namely by data reduction, tabulation of data, presentation of data, and concluding. The results in empowering the marine tribal community required local regulations to improve the community's welfare in various aspects of life. The empowerment of the Lingga marine tribe can be painted by involving collaboration between the government, the private sector, and the community.